Technical & economic interphases of the coconut industry - Ratnayake, S. B. (Pannipitiya : Stamford Lake Publications, 2005)
Study with reference to Sri Lanka.
Includes index.
Keywords: Coconut industry -- Sri Lanka; Tropical fruit; Coconut product; Agriculture; Technology